2007
DOI: 10.2337/db07-0426
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Vasculoprotective Effects of ETB Receptors in Resistance Artery Remodeling in Diabetes

Abstract: OBJECTIVE-Vascular remodeling, characterized by extracellular matrix deposition and increased media-to-lumen (M/l) ratio, contributes to the development of microvascular complications in diabetes. Matrix metalloproteinases (MMPs) play an important role in the regulation of extracellular matrix (ECM) turnover and vascular remodeling. Vasoactive factor endothelin (ET)-1 not only causes potent vasoconstriction but also exerts profibrotic and proliferative effects that change vessel architecture, which makes it a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…Structures for these compounds were reviewed in Battistini et al (2006). This treatment paradigm was based on our previous studies Sachidanandam et al, 2007Sachidanandam et al, , 2008. Treatment was maintained until sacrifice at 18 weeks of age.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structures for these compounds were reviewed in Battistini et al (2006). This treatment paradigm was based on our previous studies Sachidanandam et al, 2007Sachidanandam et al, , 2008. Treatment was maintained until sacrifice at 18 weeks of age.…”
Section: Methodsmentioning
confidence: 99%
“…However, whether and to what extent the ET B receptors contribute to this process and how diabetes affects the ET receptor profile that ultimately influences the net effect of ET-1 on cerebrovascular structure remained unknown. Building on past studies by us and others that demonstrate ET B receptors are vasculoprotective (Murakoshi et al, 2002;Sachidanandam et al, 2007), the current study tested the hypotheses that endothelial ET B receptors are decreased in diabetes and pharmacological inhibition of the ET B receptor augments vascular remodeling of middle cerebral arteries (MCAs). The rationale was that better understanding of receptor profile and function in disease states will determine the use of ET receptor subtype-selective or nonselective antagonists in the prevention of diabetic complications.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown re-cently that vascular remodeling also occurs in GK rats, and endothelin (ET)-1, a potent vasoconstrictor with profibrotic properties, mediates this effect. In this model, there is an up-regulation of the matrix metalloproteinase (MMP) system in both the systemic and cerebral circulations, contributing to vascular remodeling (Harris et al, 2005;Sachidanandam et al, 2007). The MMPs are a family of zinc-dependent enzymes that are extensively involved in vascular remodeling by regulating extracellular matrix (ECM) turnover in a very complex manner (Nagase and Woessner, 1999).…”
mentioning
confidence: 99%
“…In contrast, the selective ET A receptor blockade could attenuate this vascular remodeling in the same animals (Murakoshi et al, 2002). In addition, Sachidanandam et al (2007) reported that ET-1 contributes to the remodeling of mesenteric resistance arteries in diabetes via activation of ET A receptors, and ET B receptor-mediated action provides vasoprotective effects. Thereby, the blockade of ET B receptors may be harmful in vascular disease, and ET A receptor antagonists may be superior to ET A /ET B dual receptor antagonists in the treatment of vascular disease.…”
Section: Discussionmentioning
confidence: 95%
“…Murakoshi et al (2002) demonstrated that inhibition of ET B receptor system in a knockout mouse model or pharmacological blockade by a selective ET B receptor antagonist leads to the enhancement of vascular remodeling by the cessation of blood flow in the carotid artery. In addition, Sachidanandam et al (2007) reported that resistance artery remodeling in the diabetic rat is worsened by a selective ET B receptor antagonist, in contrast to the beneficial effect of a selective ET A receptor antagonist. These findings indicate that ET B receptor system plays a vasoprotective role in vascular remodeling.…”
mentioning
confidence: 99%